PEMBIASAAN MASYARKAT DESA MENGGUNAKAN PERPUSTAKAAN DI DESA KEPUNTEN KECAMATAN TULANGAN SIDOARJO-JAWA TIMUR - siyaswati siyaswati; Wahyu bandjarjani; Rikat Eka Prastyawan; Lambang Erwanto (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Almost all developed and progressed countries, reading activities are a necessity, as well as clothing, food and shelter needs. Reading is an important activity for having good generations that have a broad insight in everything and certainly are sensitive to the conditions of the surrounding environment. One way to grow and increase the reading interest for rural communities so that it becomes a culture is to establish a library, more precisely the Village Library. In this activity, the team of English Department formulated the problem of how the perspectives of the Kepunten Village community on reading habits in the Village Library were mainly about the procurement of the number and collection of books, reading interest, community interest, introduction, utilization and application of English literacy. The method used in seeing the results of the Devotion Program to Society (PPM) of English Language Education Program was described quantitatively. The results showed that reading habits from an early age supported by a variety of reading materials in Indonesia or English Language can encourage local people to develop themselves through village libraries supported by the local government, Devotion Programs to Society and Facilities that support the management and development of Village Libraries to better and better.